Development of Technology of Mading Shafts from 35XGCL Brand Steel Alloy - Nozimjon Kholmirzaev; Farrukhjon Abdullaev; Nodir Turakhodjaev; Mullabozorokhun Akramov; Usmon Makhamatmuratov (Researchparks Publishing, 2022)
In this paper, 35XGCL low – alloy steel alloys reduce non – metallic inclusions and gaseous pores, increasing the mechanical properties, in addition economically inexpensive energy and resource – saving technologies for the development of high – quality castings using new innovative casting technologies.